2017
DOI: 10.17221/15/2017-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The study of endometrium at gestational days 5 and 15 in dairy goats (Capra hircus)

Abstract: Zhang L., Liu X.-R., Han P., Zhou Z.-Q., Cao B.-Y., Song Y.-X. (2017): The study of endometrium at gestational days 5 and 15 in dairy goats (Capra hircus). Czech J. Anim. Sci., 62,[357][358][359][360][361][362][363][364][365][366][367][368] Endometrium receptivity, an absolutely necessary part of successful embryo implantation, and several morphological and biochemical endometrial receptivity biomarkers have already been studied and proposed in some animals. However, to our knowledge, no such a study has as ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Zhang found that the pinopodes of dairy goats also appeared only on the 15th day of gestation (RE), but not on the 5th day (PE). Moreover, the expression levels of VEGF, OPN, LIF and PRL, as markers of endometrial receptivity, are much higher in RE than PE in the endometrium of dairy goats [33]. IHC results further suggested that VEGF and OPN proteins were down-regulated and MUC1 protein was up-regulated, while no signi cant changes in LIF protein was observed after miR-431 agomir injected.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Zhang found that the pinopodes of dairy goats also appeared only on the 15th day of gestation (RE), but not on the 5th day (PE). Moreover, the expression levels of VEGF, OPN, LIF and PRL, as markers of endometrial receptivity, are much higher in RE than PE in the endometrium of dairy goats [33]. IHC results further suggested that VEGF and OPN proteins were down-regulated and MUC1 protein was up-regulated, while no signi cant changes in LIF protein was observed after miR-431 agomir injected.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies found that when GEECs were in the proliferative state, it was bene cial to the establishment of endometrial receptivity of dairy goats [33]. The expression level of CSF1 protein in human endometrium during pregnancy is much higher than that in non-pregnancy period, and the content of the placenta is also high [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The establishment of RE is a dynamic and complex process, and cell proliferation and apoptosis play an important role [ 29 ]. Our previous results have shown that miR-34a/c and miR-181a participate in the establishment of endometrial receptivity by regulating EECs apoptosis in dairy goats [ 27 , 30 ].…”
Section: Discussionmentioning
confidence: 99%